Gambling Addiction and Suicide: A 10-Year Autopsy-Based Retrospective Analysis - Şahin, Hüseyin Çağrı; Oruç, Muhammet Ali; Boylu, Muhammed Emin; Yaman, Muhammed Fatih; Üzün, İbrahim (Addicta: The Turkish Journal on Addictions, 2025)
This study retrospectively examined suicides associated with gambling disorder through a multidimensional evaluation of sociodemographic features, psychiatric comorbidities, suicide methods, and toxicological findings. Case files from Council of Forensic Medicine between September 2015 and September 2025 were reviewed. All autopsy cases classified as suicide or suspected suicide with documented gambling history or gambling-related debt were included. A total of 24 cases were identified, of whom 87.5% were male and one-third aged 18–30. Almost all cases (91.7%) had documented debts, usually bank loans or unspecified debts, and over half (54.2%) had intrafamilial problems. Bipolar disorder was the most frequent psychiatric diagnosis (66.7%), while 29.2% had prior suicide attempts. Online gambling was present in one-third of cases, associated with younger age, male sex, and a higher likelihood of hanging. Drug intoxication (37.5%) and hanging (25.0%) were the main methods, while alcohol and substance positivity were detected in 33.3% and 29.2% of cases. Findings highlight the convergence of financial strain, psychiatric disorders, and gambling behaviors, with young men emerging as a vulnerable group. These results underscore the urgency of multidisciplinary assessments and stronger regulatory frameworks. Prospective large-scale studies are also needed to refine risk profiles and guide effective prevention strategies.